Creating a Spaced Repetition Model to Supplement Education in Plastic Surgery - Zachary A. Koenig, BS; Joshua T. Henderson, MD; Sebastian M. Brooke, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. Plastic surgery encompasses a wide spectrum of material involving comprehensive anatomy, physiology, microbiology, biomaterials, complex surgical techniques, and many nonsurgical interventions. The core disciplines overlap extensively with the foundational knowledge of many other surgical specialties. With the ever-expanding knowledge base required to become a competent plastic surgeon, spaced repetition is a means to optimize learning in plastic surgery and help trainees master new concepts while retaining other facts that are easily forgotten. Platforms for spaced repetition are user-friendly and can be synchronized between devices to streamline progress and make efficient use of the limited free time that exists throughout the workday. Flashcard decks can be imported to these platforms to follow a spaced repetition algorithm. Currently, no publicly available comprehensive deck exists for education in plastic and reconstructive surgery. Creation of flashcard decks covering lectures, textbooks, or old examination questions can reinforce the foundational concepts of our field. Additionally, there is potential to improve resident performance on the Plastic Surgery In-service Training Examination. Once created, this comprehensive flashcard deck can be distributed to plastic surgery residency programs to pave the way for a uniform curriculum.